Solid Predominant Histologic Subtype in Resected Stage I Lung Adenocarcinoma Is an Independent Predictor of Early, Extrathoracic, Multisite Recurrence and of Poor Postrecurrence Survival - Ujiie, Hideki (J Clin Oncol, 2015)
PURPOSE: To examine the significance of the proposed International Association for the Study of Lung Cancer, American Thoracic Society, and European Respiratory Society (IASLC/ATS/ERS) histologic subtypes of lung adenocarcinoma for patterns of recurrence and, among patients who recur following resection of stage I lung adenocarcinoma, for postrecurrence survival (PRS). PATIENTS AND METHODS: We reviewed patients with stage I lung adenocarcinoma who had undergone complete surgical resection from 1999 to 2009 (N = 1,120). Tumors were subtyped by using the IASLC/ATS/ERS classification. The effects of the dominant subtype on recurrence and, among patients who recurred, on PRS were investigated. RESULTS: Of 1,120 patients identified, 188 had recurrent disease, 103 of whom died as a result of lung cancer. Among patients who recurred, 2-year PRS was 45%, and median PRS was 26.1 months. Compared with patients with nonsolid tumors, patients with solid predominant tumors had earlier (P = .007), more extrathoracic (P < .001), and more multisite (P = .011) recurrences. Multivariable analysis of primary tumor factors revealed that, among patients who recurred, solid predominant histologic pattern in the primary tumor (hazard ratio [HR], 1.76; P = .016), age older than 65 years (HR, 1.63; P = .01), and sublobar resection (HR, 1.6; P = .01) were significantly associated with worse PRS. Presence of extrathoracic metastasis (HR, 1.76; P = .013) and age older than 65 years at the time of recurrence (HR, 1.7; P = .014) were also significantly associated with worse PRS. CONCLUSION: In patients with stage I primary lung adenocarcinoma, solid predominant subtype is an independent predictor of early recurrence and, among those patients who recur, of worse PRS. Our findings provide a rationale for investigating adjuvant therapy and identify novel therapeutic targets for patients with solid predominant lung adenocarcinoma.